Implementation of Project Based Learning Through the STEMC Approach to Improve Students' Creative Thinking Skills - Sulastri Sulastri; Saminan Saminan; Elisa Elisa; Yusrizal Yusrizal; Ibnu Khaldun; Latifah Hanum; Ismi Zatya Iskandar (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this study was to investigate the improvement of students' creative thinking skills by implementing STEMC-based project-based learning. This study consisted of 52 students of class X science at SMAN 3 Langsa. Creative thinking ability was assessed through pretest-posttest which was tested using statistically paired sample t-test and N-gain test. The results of the study stated that the application of the STEMC-based PjBL model on electrolyte and nonelectrolyte materials had increased creative thinking skills at a significant level of 0.000, indicating a sig value <0.05 and the results of the N-gain calculation were 0.8 in the high category. The results of the analysis showed that there were differences in the improvement of creative thinking skills before and after the application of the STEMC-based PjBL model. The results of the N-gain of each indicator of creative thinking ability, namely 0.47 elaboration are classified in the medium category, while flexibility, fluency and originality with N-gain results of 0.97, 0.87, and 0.8 are classified in the high category